Inulin Extraction from Different Types of Tubers in Magelang District - Lilis Hartati; Mohamad Haris Septian; Noor Alif Fitria; Rahma Wulan Idayanti; Mikael Sihite (JURNAL ILMIAH PETERNAKAN TERPADU, 2023)
This study aimed to determine the levels and characteristics of inulin contained in various types of tubers in Magelang district. The samples used were honey sweet potato (Ipomoea batatas L.), purple sweet potato (Ipomoea batatas L.), white sweet potato (Ipomoea batatas L.), gadung (Dioscorea hispida), yam (Dioscorea alata L.), canna (Canna edulis Ker.), and arrowroot (Maranta arundinacea). The variables observed were yield, inulin content, inulin production, water content of the yield, yield solubility, and the degree of acidity (pH) of the yield. The research results obtained from 7 tubers, the highest yield was arrowroot tubers (0.155%). Honey sweet potato gave the lowest yield (0.035%), with the highest inulin content (6.472%), the highest water content (14.385%), and the highest solubility (0.685%). Arrowroot tubers gave the highest yield but the lowest inulin content. The highest inulin production is found in purple sweet potato. The degree of acidity (pH) of the tuber extract was in the range of 4.97-5.96. The conclusion of this study is that different types of tubers produce different content and production of inulin.